Model Pembelajaran Bahasa Berbasis Riset melalui Analisis Framing - Suharyo Suharyo (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
This study aims to apply a number of language learning models in research-based tertiary institutions through framing analysis. Experimental learning models such as discovery learning, inquiry learning, dan problem based. The results of the teaching and learning process were responded well by a numbe r of students. The response, for example, is demonstrated through research (linguistic) using framing analysis for the final project preparation (thesis). Meanwhile, in the context of research: the methods used include: consider, record, with data analysis using framing analysis. The result: in framing both (Jokowi and Prabowo) there are similarities in terms of (1) protruding at the syntactic level, namely on the headline, (2) protruding on the script aspect, ie focusing on reporting, (3) highlighting on the aspect of the theme, namely in paragraphs, and (4) protruding on the rhetorical aspect, i.e. the photos displayed. In addition, there is a negative image of Prabowo more visible than in Jokowi.